A roda da vida: revelações de uma paciente em hemodiálise. - Xavier, Suênia Silva de Mesquita (2011)
Reconstruct, from listening, the life histories of a chronic renal patient, submitted to hemodialysis, is the objective of this investigation. How methodological procedure,we worked with oral history of life, ,according Meihy, within a qualitative approach. For this, we had the approval of the Ethics Committee in Research of Hospital Universitário Onofre Lopes (HUOL), under protocol no 591/2011. As instrument to approach the patient, we did interviews with open questions, conducted in the patient's house. There were five meetings, in which we hear his story, experiences and ways of coping during their course of illness and treatment. The analysis was based on the collaborator's narratives, anchored in studies dealing with oral history, of human subjectivity, highlighting the resilience, as indicated Cyrulnik. Her story leads us to conclude that despite the adversities of life and suffering, there is in humans, the strength to navigate the streams and be happy. This is the lesson that leaves us the collaborator this study.